2008
DOI: 10.1097/mao.0b013e31816fdc90
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Versus Transcutaneous Bone Conduction Implant System

Abstract: Present results support the proposal that a BCI system can be a realistic alternative to a BAHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 11 publications
4
60
0
4
Order By: Relevance
“…Moreover, evidence is mounting that, even for the percutaneous BAHA, there is an increased need for more power, not less. However, it has been shown in earlier studies on a dry skull and on cadaver heads that the sensitivity to bone conducted sound would increase if the excitation point approaches cochlea (Stenfelt et al, 2000;Stenfelt et al, 2005;Håkansson et al, 2008;Eeg-Olofsson et al, 2008). This phenomenon seems to be related to the fact that the excitation point moves from the thinner parietal region of the skull bone to the interior portion of the temporal bone and closer to the cochlea.…”
Section: Figure 1: Principal Design Of a Generic Percutaneous Bone Anmentioning
confidence: 71%
See 4 more Smart Citations
“…Moreover, evidence is mounting that, even for the percutaneous BAHA, there is an increased need for more power, not less. However, it has been shown in earlier studies on a dry skull and on cadaver heads that the sensitivity to bone conducted sound would increase if the excitation point approaches cochlea (Stenfelt et al, 2000;Stenfelt et al, 2005;Håkansson et al, 2008;Eeg-Olofsson et al, 2008). This phenomenon seems to be related to the fact that the excitation point moves from the thinner parietal region of the skull bone to the interior portion of the temporal bone and closer to the cochlea.…”
Section: Figure 1: Principal Design Of a Generic Percutaneous Bone Anmentioning
confidence: 71%
“…When comparing the promontory acceleration levels measured by a laser Doppler vibrometer (LDV) through the ear canal it was found that this first version of the BCI had a similar or even higher Maximum Power Output (MPO) as compared to a Classic Baha ® . This was a positive and partly unexpected result, as previous dry skull measurements had In the paper by Håkansson et al 2008 it was also discussed how the implanted transducer could be installed with a safe and minimally invasive surgery. Obviously, the screw attachment and coupling used in that study on the cadaver head should not be used in live human skulls for several reasons: (1) to drill and install a screw interiorly from a bottom plane in a recess in the lateral portion of the temporal bone is associated with a high risk for facial nerve or vestibular damage, (2) the spongeous quality of the bone might not give a stable and firm attachment, (3) the screw length and snap coupling creates an extra height of 8-10 mm that should be added to the height of the transducer casing resulting in a total distance of 16-20 mm into the temporal bone and (4) would most likely need a two stage surgical procedure.…”
Section: Figure 1: Principal Design Of a Generic Percutaneous Bone Anmentioning
confidence: 94%
See 3 more Smart Citations